Individual behavioral differences and health of golden‐headed lion tamarins (Leontopithecus chrysomelas). Issue 5 (3rd March 2020) - Costa, Thaise S. O.; Nogueira‐Filho, Sérgio L. G.; De Vleeschouwer, Kristel M.; Oliveira, Leonardo C.; de Sousa, Maria Bernardete C.; Mendl, Michael; Catenacci, Lilian S.; Nogueira, Selene S. C.
Abstract: Individual behavioral differences may influence how animals cope with altered environments. Depending on their behavioral traits, individuals may thus vary in how their health is affected by environmental conditions. We investigated the relationship between individual behavior of free‐living golden‐headed lion tamarins ( Leontopithecus chrysomelas ) responding to a novel object (to assess exploration‐avoidance), and their habitat use and health status (endoparasitism; clinical measures: biometric data, heart rate, respiratory frequency, and temperature; fecal glucocorticoid metabolites). As parasite transmission can be affected by individual variation in social contact and social grooming, we also evaluated whether more sociable individuals show higher endoparasite loads compared with less sociable animals. Four groups living in landscapes with different levels of human disturbance were investigated: two in degraded forest fragments in an agricultural matrix (DFAM—higher disturbance), and two in a cocoa agroforestry system ( cabruca —lower disturbance) in the Atlantic forest of South Bahia, Brazil. Using a subjective ratings approach, highly correlated adjective descriptors were combined to produce z ‐score ratings of one derived variable ("confidence"), which was selected to characterize the tamarins' exploration/avoidance responses during a novel object test. The higher the confidence score, the longer female tamarins spent foraging for prey independent of landscape, and the greater their body mass independent of sex and landscape. Only DFAM individuals showed intestinal parasite infection. Endoparasite loads were positively correlated with the number of grooming partners, suggesting an association between social grooming and transmission (more groomers = more endoparasites). Individual behavior, including in a test situation, may thus have some predictive value for behavior in a free‐living context, and for its health consequences. Abstract : Only DFAM individuals showed intestinal parasite infections and their parasite loads were correlated with the number of grooming partners they had, suggesting an association between grooming and infection transfer. High "confident" individuals in DFAM landscape spent more time foraging for prey. Research Highlights: Individual behavioral responses to novelty were correlated with foraging for animal prey. Only individuals from degraded area showed intestinal parasite infections. The parasite loads were correlated with the number of grooming partners.